2019
DOI: 10.1002/aelm.201900348
|View full text |Cite
|
Sign up to set email alerts
|

All‐Transparent Oxide Photovoltaics: AZO Embedded ZnO/NiO/AgNW Band Selective High‐Speed Electric Power Window

Abstract: generate energy from the invisible radiation of the sun, while protecting us from harmful UV radiation and pollution, by employing the essential elements of a net-zero emission energy system. [3,4] The EPW is driven by UV light while simultaneously transmitting the visible spectrum, and in this way offers onsite energy generation to power micro-scale devices, for example, the internet of things. [3][4][5][6] To be environmentally effective, the system should be made from sustainable materials such as metal-oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 47 publications
0
22
0
1
Order By: Relevance
“…[ 6,7 ] To date, state‐of‐the art UV‐selective solar cells are mainly based on the use of ZnO as the absorber material. [ 8–13 ]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[ 6,7 ] To date, state‐of‐the art UV‐selective solar cells are mainly based on the use of ZnO as the absorber material. [ 8–13 ]…”
Section: Figurementioning
confidence: 99%
“…[6,7] To date, state-of-the art UV-selective solar cells are mainly based on the use of ZnO as the absorber material. [8][9][10][11][12][13] However, there are some important caveats that limit the use of ZnO for such solar cells. First, related to polarity and charge transport properties, being the fact of lack of bipolarity (i.e., p-type ZnO) which prevents the fabrication of homojunctions in conventional p-n configuration and also the synthesis of p-ZnO as absorber.…”
mentioning
confidence: 99%
“…A literature review indicated that inorganic TPVs have attracted considerable research interest since 2013 because of the improvements in photovoltaic performance, facilitated by the incorporation of various mechanisms, to overcome the factors that limit device efficiency [15,[33][34][35][36][37][38][39][40][41][42][43]. Over the past few years, several research groups have reviewed the technologies underlying TPVs, semi-transparent thin-film TPVs, and organic TPVs [6,26,[44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…In the TPVs, the p-n heterojunction is typically prepared using the reactive sputtering technique, and consequently, this review article highlights the optoelectrical properties of the reactivesputtered wide-band-gap metal-oxide films. II compares the optical and electrical properties of these metal oxides along with their deposition parameters [37,39,[47][48][49][50][51][52][53][54][55][56][57][58][59]. Figure 3 presents an energy-level diagram of both the p-type and n-type metal oxides [33,[60][61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…State-of-theart inorganic UV-selective solar cells are mainly based on the use of ZnO or Zn(O,S) as the absorber material, but even though presenting high average visible transparency (AVT) values, they still have to overcome an efficiency limited to around 0.5%. [15][16][17][18][19] However, recently, there have been demonstrations on implementing a-Si:H in UV-selective metal-oxide-based solar cells, showing the possibility to overcome this PCE limitation, but at the cost of losing some transparency. [20] The use of a-Si based technologies in this emerging field of PV has added benefits in terms of the use of materials that are stable and durable, that are not deemed as critical raw.…”
Section: Introductionmentioning
confidence: 99%